Learning and Capacity Building for Persons with Disabilities through a Strengths-Based Perspective: Assessment of the ROPES Framework in the 'Tumbuh Mandiri' Farmers Group - Wahida, Dian Salma; Raharjo, Santoso Tri; Humaedi, Sahadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Persons with disabilities continue to face various challenges, including dependence on external assistance, limited access to economic resources, non-inclusive policies, and programs that have not fully supported sustainable independence. This study offers an alternative perspective by applying a strengths-based approach, which views persons with disabilities as individuals with potentials, capacities, and resources that can be developed. The analysis employs the ROPES framework (Resources, Options, Possibilities, Exceptions, and Solutions) proposed by Clay Graybeal to identify individual and collective strengths. Using a qualitative descriptive method, this study explores the lived experiences and capacities of persons with disabilities within their social context. The research was conducted among members of the “Tumbuh Mandiri” Disability Farmers Group in Cimahi City, Indonesia. Informants consisted of one group leader and two administrators selected through purposive sampling. The findings indicate that strengths-based and experiential learning processes within the group play a significant role in fostering members’ social and economic independence. These results suggest that a strengths-based approach provides an important foundation for designing inclusive, sustainable, and capacity-oriented disability empowerment programs.Persons with disabilities continue to face various challenges, including dependence on external assistance, limited access to economic resources, non-inclusive policies, and programs that have not fully supported sustainable independence. This study offers an alternative perspective by applying a strengths-based approach, which views persons with disabilities as individuals with potentials, capacities, and resources that can be developed. The analysis employs the ROPES framework (Resources, Options, Possibilities, Exceptions, and Solutions) proposed by Clay Graybeal to identify individual and collective strengths. Using a qualitative descriptive method, this study explores the lived experiences and capacities of persons with disabilities within their social context. The research was conducted among members of the “Tumbuh Mandiri” Disability Farmers Group in Cimahi City, Indonesia. Informants consisted of one group leader and two administrators selected through purposive sampling. The findings indicate that strengths-based and experiential learning processes within the group play a significant role in fostering members’ social and economic independence. These results suggest that a strengths-based approach provides an important foundation for designing inclusive, sustainable, and capacity-oriented disability empowerment programs.